Pattani’s Architectural Epitome of the Yaring Palace: Journeying the Historical Phases of a Regional Design Language - Mohd Jaki Mamat; Puteri Shireen Jahn Kassim; Noor Hanita Abdul Majid (Universitas Indraprasta PGRI, 2019)
This paper uses the case of the exquisite design Yaring palace as a framework and springboard to discuss the particularities of the design language of the Pattani palace and architecture. The region of Pattani represents a unique crossing between a Thai identity and a Malay identity in terms of architecture. Because of its geographic position, both Asian identities merge into a language of regionalism syncretism that creates a rich blend of architectural expression representative of a South East Asian language. The paper discusses its facade expression, ornamentation, layout and interior design elements.